PENERAPAN MODEL KOOPERATIF TIPE THE POWER OF TWO UNTUK MENINGKATKAN KERJASAMA DAN HASIL BELAJAR - Marti Mira (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
This study is purposed to describe the implementation of cooperative learning the power of two type to improve the students’ cooperation, learning outcomes, and the effectivity on the implementation of cooperative learning the power of two type in improving the students’ learning outcomes. The study was held by using Classroom Action Research (CAR) and quasi experiment. The subject of the CAR was class XI IPS 3 of SMAN 03 Mukomuko, class XI IPS 2 of SMAN 03 as the experiment class and class XI IPS 1 as the control class. This research used total sample and observation method. Observation sheet were used to measure the teacher’s ability in implementing the learning model and the students’ ccooperation and also written test to measure the improvement of the student’s learning outcomes. The data were gained then analyzed according to the type of the data, the qualitative data were analyzed qualitatively and also the quantitative one that was analyzed by using average formula and  dependent and independent sample t-test. Based on the research during three cycles in class XI IPS 3, the result of the analysis showed that the teacher’s ability in implementing the learning model got some improvement during the implementation.  The students’ cooperation and their learning outcomes got some improvements from the first until the third cycle following the teachers’ ability in implementing the cooperative learning model the power of two type. The conclusions of the research were the implementation of cooperative learning model the power of two type was able to improve the students’ cooperation and their learning outcomes, the implementation of cooperative learning model the power of two type was more effective to improve the students’ learning outcomes than the conventional model on economy subject in class XI IPS of SMAN 03 Mukomuko.